Redefining the situation : the writings of Peter McHugh - Bonner, Kieran, 1951-; Raffel, Stanley; McHugh, Peter, 1929-2010 (McGill-Queen's University Press, 2019)
"Peter McHugh (1929-2010) was an internationally known sociologist within the field of anti-positivist social theory. As the only selection of McHugh's sole-authored writings, Redefining the Situation presents a comprehensive yet surprising view of this key theorist's influence in this field. Redefining the Situation is a compendium of McHugh's published and unpublished short-form writings, along with three new essays on McHugh's work that include an original essay by his long-time collaborator and friend Alan Blum. The collection contributes to the project of reinventing social theory by providing a new perspective from which to imaginatively rethink the development of sociology over the last fifty years. It locates McHugh's work not only within the modern and postmodern sociological tradition but also within contemporary social theory broadly, including hermeneutics, critical theory, deconstruction, and Hannah Arendt's political theory. The essays and articles in this volume show the development of a method to analyze everyday behaviour in light of fundamental questions, exploring conflicts and connections between socialization and recidivism, fragmentation and ethnic cleansing, justice and affirmative action, teaching and university politics, and intimacy and aesthetics. It shows how we can move beyond contemporary debates about big data/postmodernism, and along the way develops convergences in Anglo-American and Continental thought. By tracing the development of the tradition of social inquiry, Analysis, from its beginnings until today, Redefining the Situation re-establishes a prominent sociologist as one of the leading intellectuals in the field of interpretive social theory."--